Potential factors causing failure of whole plant nettle (Urtica cannabina) silages - Huang, Rongzheng; Chen, Yongcheng; Ma, Chunhui; Chai, Yuxin; Jia, Shuan; Zhang, Fanfan (Frontiers in Microbiology, 2023)
The present study investigated the potential factors causing nettle silage failure through metabolome and bacterial community composition analyses during ensiling. During ensiling, the pH was > 6.22, and water-soluble carbohydrate and organic acid contents stabilized after 7 d. At the genus level, Enterococcus, Pediococcus, and Weissella were the dominant bacteria, with stable trends, whereas Lactococcus and Enterobacter relative abundance decreased significantly over time. Lactobacillus relative abundance was < 1% during the entire ensiling period, and malic acid metabolic pathway was the most important pathway. Enterococcus, Pediococcus, and Weissella were negatively correlated with malic acid, with Lactobacillus displaying an opposite trend. The results suggested that Lactobacillus activity was the lowest among lactic acid bacteria (LAB) during ensiling, which is the main reason for nettle ensiling failure, and attributable to a low capacity to compete for fermentation substrates such as malic acid against other LAB during ensiling. Additionally, anti-bacteria activity of nettle probably inhibited Enterobacter activity during ensiling.